Solar-powered irrigation in Nepal: implications for fossil fuel use and groundwater extraction - Kafle, Kashi; Balasubramanya, Soumya; Stifel, D.; Khadka, Manohara (IOP Publishing, 2024)
In recent years, use of solar-powered irrigation pumps (SIPs) has increased significantly in the agricultural plains (terai) of Nepal. Federal and local governments there have subsidized the pumps in an effort to expand irrigated agriculture using renewable energy. We use data from a cross-sectional survey of 656 farming households in the terai to examine how SIPs affect fossil fuel use and groundwater extraction. We find that most SIP users continued to use their fossil-fuel pumps, as very few completely replaced them with solar pumps. Farmers who received SIPs operated their irrigation pumps more hours than those who did not receive SIPs. Taken together, these findings suggest that groundwater use has increased, as SIP recipients ‘stack’ their pumps. We also find that solar pumps were more likely to be owned by richer households and those with better social networks than those who were poorer and had relative social disadvantage. As Nepal expands the use of solar pumps in agriculture, policy efforts may benefit from managing expectations about the carbon-mitigation potential of this technology, managing groundwater risks as SIP use expands, and making SIPs more inclusive.